The mathematical dictation role in teaching mathematics in primary school - M.A. Kodirova; L.A. Muydinov; Kh. Yuldasheva (International Journal on Orange Technologies, 2020)
The article aims to consider the testing knowledge, skills and abilities effect with the mathematical dictation help in primary grades.